Peningkatan Keterampilan Kader Posyandu Melalui Pelatihan Pengolahan Ikan Nila - Rita Kurnia Apindiati; Syarif Irwan Nurdiansyah; Shifa Helena (Indonesian Journal Publisher, 2024)
Increasing skills in processing nutritious food is an important step in efforts to improve public health. One source of protein needed by the human body, especially during the growth and development period, is fish and its derivatives. Fish nuggets are a preparation made from sea fish or freshwater fish, which can practically be consumed as a side dish or snack. The aim of this training is to provide knowledge and skills to Posyandu cadres in processing tilapia fish into nuggets that are healthy, delicious and highly nutritious, so that they can become a healthy food alternative for families and local communities. The activity was attended by 15 participants, including posyandu cadres at the Mekar Baru Village Community Health Center. The activity was carried out using educational lecture methods and practice in making nuggets made from tilapia fish. The activity evaluation was carried out using a questionnaire method, namely pretest and posttest, and the results of the evaluation showed that there was a percentage increase in the participants' understanding and skills in processing nuggets made from tilapia fish.